Vitamin D linked to high blood pressure (Research, Society and Development, 2020)
The aim of the review was to verify the link between vitamin D and hypertension. The study is an integrative review based on the search for articles in the PubMed, Lilacs and Scielo databases, using as descriptors: “Vitamin D” associated with “hypertension”, “metabolic syndrome” and “cardiovascular diseases”. All researched in Portuguese and English. Original and review articles published from 2007 to 2018 were included. It was found that the majority of studies already conducted found interaction between hypovitaminosis D and the onset of hypertension, recommending the association of solar and dietary sources. supplementation to achieve significant levels of prevention. However, many authors highlight the absence of association, and when present, it is not significant, which suggests the development of new studies.